Efficacy of tranexamic acid in preventing postpartum haemorrhage in vaginal delivery - Satyavathi, G. Anantha Lakshmi; K., Chandrika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Postpartum blood loss is difficult to evaluate especially in developing countries like India where most of the women are anaemic with poor reserve and these conditions are further aggravated by increased demand during pregnancy and blood loss during third stage of labour. The present study was planned to compare the efficacy of prophylactic 10 IU intramuscular oxytocin and 10 IU intramuscular oxytocin +1g Tranexamic acid in reducing blood loss in the third stage of labour. Methods: The present study was carried out on full term pregnancies primigravida/ multiparas with singleton pregnancy being delivered vaginally at GSL Hospital, Rajahmundry between 2016-2017 were included. For this comparative study, 200 women in labor were included after obtaining informed consent. A detailed obstetric history, history of previous medical illnesses, history of the treatment received earlier, cardiovascular and respiratory system and other systems including thyroid and breast were noted. Results: The average total blood loss in IIIrd stage of labour with IM oxytocin was 210 ml and with IM oxytocin + Tranexamic acid was130 ml, which was statistically significant (p<0.001). Oxytocin + Tranexamic acid group had less blood loss when compared to oxytocin group alone. Side effects like, nausea vomiting, headache were slightly more with oxytocin + Tranexamic acid group when compared to oxytocin group alone. Conclusions: In the active management of IIIrd stage of labour 10 IU intramuscular Oxytocin + one gram of tranexamic acid IV is a better combination in reducing the blood loss at delivery when compared to 10 IU intramuscular oxytocin alone.